Pengaruh Struktur Modal dan Kebijakan Dividen Terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Moderating pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2020-2022 - Agustina Irawati; Kurnia Rina Ariani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of capital structure and dividend policy on firm value, with profitability as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 period. This research employs a quantitative approach using multiple linear regression analysis. The data used is secondary data obtained from company financial reports, selected through purposive sampling based on specific criteria. The results indicate that capital structure and dividend policy do not significantly affect firm value. This suggests that investors prioritize operational efficiency and business strategy over capital structure and dividend policy. Furthermore, profitability does not directly impact firm value but weakens the effect of capital structure and dividend policy on firm value. Low profitability reduces investment attractiveness, limits funding optimization, and restricts dividend distribution, ultimately leading to a decline in firm value. The findings of this study provide managerial implications for designing more effective financial strategies to enhance investment appeal. Future research is recommended to include additional variables for a more comprehensive analysis.